‘Arkhat’ - a new spring soft wheat variety for the conditions of Povolzhie and Urals - V. G. Krivobochek; S. V. Kosenko; I. F. Demina (Зерновое хозяйство России, 2018)
The article presents the data about a new spring soft wheat variety ‘Arkhat’ which has a realized potential of productivity (5.5 t/ha) and can produce valuable grain. The variety is protected by the patent as a special breeding achievement and is recommended to introduce into the State List and to use in Volga-Vyatka, Middle Volga and Ural regions of RF. The variety is middle maturing with high general and special adaptive ability. It possesses an important biologic feature: the variety is tolerant to drought and high temperatures and has good responsiveness to humidity. The variety has a strong stem, it is high resistance to lodging. The technological traits of grain meet the demands for valuable and strong wheat of first and second group of quality: test weight of 675…773 g/l, vitreousness 65…90%, protein content in kernels 13.8…17.0%, gluten content in kernels 30.0…35.6%. Baking properties of the variety ‘Arkhat’ are excellent; the variety has been added into the List of valuable wheat according to the decision of State Commission of RF for testing and protection of breeding achievements. The gene Y, concatenated with the gene of resistance to brown rust Lr 19 and in combination with the gene Lr 34, inherited from the variety ‘Isheevskaya’ gives to the variety resistance to brown rust and is responsible for yellow color of the flour. In 2014 the productivity of 5.18 t/ha was obtained on the Arsk plot of the Republic of Tatarstan. In the competitive testing the variety ‘Arkhat’ produced the maximum yield of 5.49 t/ha in 2009.